Access and quality of maternity care for disabled women during pregnancy, birth and the postnatal period in England: data from a national survey. Issue 7 (20th July 2017) - Malouf, Reem; Henderson, Jane; Redshaw, Maggie
Abstract : Objectives: More disabled women are becoming mothers, and yet, their care is rarely the focus of quantitative research. This study aimed to investigate access and quality of maternity care for women with differing disabilities. Design: Secondary analysis was conducted on data from a 2015 national survey of women's experience of maternity care. Descriptive and adjusted analyses were undertaken for five disability groups: physical disability, sensory impairment, mental health disability, learning disability and multiple disability, and comparisons were made with the responses of non-disabled women. Setting: Survey data were collected on women's experience of primary and secondary care in all trusts providing maternity care in England. Participants: Women who had given birth three months previously, among whom were groups self-identifying with different types of disability. Exclusions were limited to women whose baby had died and those who were younger than 16 years at the time of the recent birth. Results: Overall, 20, 094 women completed and returned the survey; 1958 women (9.5%) self-identified as having a disability. The findings indicate some gaps in maternity care provision for these women relating to interpersonal aspects of care: communication, feeling listened to and supported, involvement in decision making, having a trusted and respected relationship with clinical staff. Women from all disability groups wanted more postnatal contacts and help with infant feeding. Conclusion: While access to care was generally satisfactory for disabled women, women's emotional well-being and support during pregnancy and beyond is an area that is in need of improvement. Specific areas identified included disseminating information effectively, ensuring appropriate communication and understanding, and supporting women's sense of control to build trusting relationships with healthcare providers.